GAD antibody-spectrum disorders: progress in clinical phenotypes, immunopathogenesis and therapeutic interventions. (March 2021) - Tsiortou, Popianna; Alexopoulos, Harry; Dalakas, Marinos C.
Antibodies against glutamic acid decarboxylase (GAD), originally linked to stiff person syndrome (SPS), now denote the " GAD antibody-spectrum disorders " ( GAD-SD ) that also include autoimmune epilepsy, limbic encephalitis, cerebellar ataxia and nystagmus with overlapping symptomatology highlighting autoimmune neuronal excitability disorders. The reasons for the clinical heterogeneity among GAD-antibody associated syndromes remain still unsettled, implicating variable susceptibility of GABAergic neurons to anti-GAD or other still unidentified autoantibodies. Although anti-GAD antibody titers do not correlate with clinical severity, very high serum titers, often associated with intrathecal synthesis of anti-GAD-specific IgG, point to in-situ effects of GAD or related autoantibodies within the central nervous system. It remains, however, uncertain what drives these antibodies, why they persist and whether they are disease markers or have pathogenic potential. The review, focused on these concerns, describes the widened clinical manifestations and overlapping features of all GAD-SD; addresses the importance of GAD antibody titers and potential significance of GAD epitopes; summarizes the biologic basis of autoimmune hyperexcitability; highlights the electrophysiological basis of reciprocal inhibition in muscle stiffness; and provides practical guidelines on symptomatic therapies with gamma-aminobutyric acid-enhancing drugs or various immunotherapies.